The inverse scattering method of general relativity - Eygi, Esat Erdem. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
In this thesis, the Inverse Scattering Method of Belinski and Zakharov is studied in the context of general relativity. The physical interpretation of solitons is estab lished, as well as the connection between solitons and Weyl Class solutions. The single-source and double-source solutions of Einstein’s equations are generated by the Belinski-Zakharov method. The event horizons of single compact objects and binary compact objects are illustrated. The surfaces are isometrically embedded into Eu clidean three-space, hyperbolic three-space by the half-space model, and hyperbolic three-space by the Poincare ball model.
Keywords: General relativity (Physics)